2018
DOI: 10.1002/jcp.26395
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in cutaneous melanoma: Role as diagnostic and prognostic biomarkers

Abstract: Melanoma is the leading cause of skin cancer deaths in the United States, and its incidence has been rising steadily for the past 30 years (Aftab, Dinger, & Perera, 2014). A more complete understanding of the molecular mechanisms that drive melanomagenesis is crucial to improve diagnosis, prognostication, and treatment of this disease. Given that melanoma survival rates are better when the disease is detected early, precise diagnostic tests for early melanoma detection would be extremely useful. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 72 publications
0
49
0
Order By: Relevance
“…The effects of preclinical and clinical research on miRNAs is undeniable, especially in cancer research, because several miRNAs have been identified and validated as diagnostic and prognostic biomarkers and even pharmacological targets (Botta et al, ; Jafri, Zaidi, Ansari, Al‐Qahtani, & Shay, ; Litwinska & Machalinski, ; Ross, Kaushik, Valdes‐Rodriguez, & Anvekar, ; Siano et al, ). Therapeutic intervention targeting miRNAs dysregulation is aimed at (a) increasing the expression of a down‐regulated miRNA with gene therapy and (b) decreasing the expression of an up‐regulated miRNA through anti‐miRNAs, named also antagomirs (Flemming, ; Svoronos, Engelman, & Slack, ; Wahlquist et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of preclinical and clinical research on miRNAs is undeniable, especially in cancer research, because several miRNAs have been identified and validated as diagnostic and prognostic biomarkers and even pharmacological targets (Botta et al, ; Jafri, Zaidi, Ansari, Al‐Qahtani, & Shay, ; Litwinska & Machalinski, ; Ross, Kaushik, Valdes‐Rodriguez, & Anvekar, ; Siano et al, ). Therapeutic intervention targeting miRNAs dysregulation is aimed at (a) increasing the expression of a down‐regulated miRNA with gene therapy and (b) decreasing the expression of an up‐regulated miRNA through anti‐miRNAs, named also antagomirs (Flemming, ; Svoronos, Engelman, & Slack, ; Wahlquist et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Node colour (from blue to red) is proportional (temperature scale) to node grade value. Edge thicknesses are proportional to edge betweenness values immunohistochemistry showed that in the inner plexiform layer (IPL) of diabetic mice, there was a significant decrease of BDNF staining (Figure 7), both in 5-(twofold decrease) and 10-week (threefold decrease) diabetic mice, compared to control.4 | DISCUSSIONThe effects of preclinical and clinical research on miRNAs is undeniable, especially in cancer research, because several miRNAs have been identified and validated as diagnostic and prognostic biomarkers and even pharmacological targets(Botta et al, 2017;Jafri, Zaidi, Ansari, Al-Qahtani, & Shay, 2015;Litwinska & Machalinski, 2017;Ross, Kaushik, Valdes-Rodriguez, & Anvekar, 2018;Siano et al, 2018). Therapeutic intervention targeting miRNAs dysregulation is aimed at (a) increasing the expression of a down-regulated miRNA with gene therapy and (b) decreasing the expression of an upregulated miRNA through anti-miRNAs, named also antagomirs…”
mentioning
confidence: 97%
“…miRNAs have been investigated in various malignancies, including melanoma. Studies revealed that miRNAs were aberrantly expressed at different stages of melanoma, and they have been identified as potential diagnostic and prognostic biomarkers (Ross, Kaushik, Valdes‐Rodriguez, & Anvekar, ). miR‐142‐3p is a tumor suppressor in many tumors and it can regulate autophagy (Y. Lu et al, ; Mansoori et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma has a high mortality burden if not detected early (1,2). The histopathological differentiation of benign pigmented lesions (melanocytic and Spitz nevi) and malignant melanoma often presents a diagnostic challenge, driving recent efforts to develop novel biomarkers (3,4). Moreover, there continues to be a need to identify molecular master regulators and checkpoints to target with novel drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there continues to be a need to identify molecular master regulators and checkpoints to target with novel drugs. Over the past decade, micro-(mi)RNAs have emerged as promising diagnostic, therapeutic, and theranostic candidates due to their emerging roles in melanoma hallmarks including proliferation, migration, apoptosis, immune responses, and in shaping the tumor niche (4,5).…”
Section: Introductionmentioning
confidence: 99%